(untitled) (AYUSHDHARA, 2022)
COVID-19, is a disease caused by the novel corona virus SARS-CoV-2 hat shows symptoms like flu or may even remain asymptomatic. Most people who develop Covid 19 recover, but current evidences suggest that, approximately 10 % to 20% people experience a lot of effects after they recover from this illness. The common symptoms include headache, sleep problems, depression or anxiety, fatigue, post-exertional malaise, difficulty breathing, rashes and sometimes recurrence of fever itself. These mid and long term effects are collectively called as post covid 19 conditions. The patients visiting the post covid clinics are increasing day by day. The researchers are working with patients who develop post covid 19 condition to better understand about its causes, symptoms and effects. In this current situation, it is very important to analyse this in an Ayurvedic perspective. Ayurveda has mentioned a condition called Punaravartaka jwara, in the context of Jwara chikitsa in Caraka Samhita that describes that, if a person, who has become free from jwara, resorts to prohibited factors before gaining strength, then the Jwara may reappear. Sometimes, the Dosas causing Jwara undergo Paripaka in the Dhatus and the Jwara may subside but manifest later as harmful symptoms like, Dīnata, Svayathu, Glani, Panduta, loss of appetite, itching, urticaria, pimples and suppression of the power of digestion. So, the manifestation of Punaravartaka Jwara has similarity with the post covid 19 conditions. So, the present article aims to review the analogy of the contributing factors and clinical presentation of Punaravartaka jwara and post covid condition and to plan a treatment protocol